Stota obletnica prvega državnega prvenstva v smučanju - Pustovrh, Janez (Šport (Ljubljana), 2021)
This year we are celebrating the hundredth anniversary of the organization of the first national skiing championship. The Winter sports section of the Slovenian Sports Association, led by Rudolf Badjura and Joso Gorec, laid the foundations of competitive skiing in Slovenia by organizing the national championship of the then state. On the slopes of Bohinjska Bistrica, a small number of enthusiasts in cross-country skiing and ski jumping competed against each other and plowed the competitive fallow of the increasingly popular sport, which eventually began to embody national identity. Generations of Slovene competitors, who in the post-war period also reached the connection to the top of the world, grew up on the modest foundations of enthusiastic beginners, both organizers and competitors. And on the occasion of the 100th anniversary, Slovenian skiers reached a record milestone in terms of winning the number of medals at one world championship in Nordic skiing.
Keywords: cross-country skiing; državna prvenstva; history of skiing; national championships; ski jumping; skiing; smučanje; smučarski skoki; smučarski teki; sport; šport; zgodovina smučanja